Association between parent–adolescent communication about sex-related topics and HIV testing, United States. 2006–2013. Issue 3 (4th March 2017) - Balaji, Alexandra B.; Oraka, Emeka; Fasula, Amy M.; Jayne, Paula E.; Carry, Monique G.; Raiford, Jerris L.
ABSTRACT: Adolescents need information about sex-related topics in order to reduce risk behavior and engage in healthy sexual decision-making. Parents have the potential to be an important source of this information. Using the 2006–2010 and 2011–2013 National Survey of Family Growth, we examined associations between parent–adolescent communication before age 18 about sex-related topics and HIV testing among respondents aged 18–24 that ever had sexual intercourse (women = 3893; men = 3359). Analyses showed that for both men and women, discussing how to prevent HIV/AIDS and how to use a condom with a parent before age 18 were positively associated with HIV testing. Among women only, discussions about methods of birth control, where to get birth control, and STDs were positively associated with HIV testing. Developing strategies and interventions to facilitate parent–adolescent communication about sex-related topics, particularly HIV prevention and condom use, may be important to increase HIV testing among young women and men.